Affective Infrastructures: Toward a Cultural Neuropsychology of Sport - Heywood, Leslie L. (Frontiers in Evolutionary Neuroscience, 2011)
Recently researchers within sport studies have argued that the traditional focus on clinical psychology and performance enhancement is incomplete, and emphasize athletes’ social and familial contexts in a paradigm that examines movement, cognition, and emotion. But this model is still incomplete since it is missing a fundamental variable—our evolutionary neurobiological roots. Affective neuroscience shows that because sport so clearly activates neural systems at the ultimate level of causation, it can be seen to serve fundamental needs for affective balance. A neurobiology of affect shows how the evolution of the mammalian autonomic nervous system has resulted in neurophysiological substrates for affective processes and stress responses, and has wide-ranging implications for sport studies by suggesting what forms of coaching might be most effective. I propose “cultural neuropsychology of sport” to describe a model that examines relationships between neurophysiological substrates and athletes' social and familial contexts, and how these variables facilitate athletes’ neuroceptions of safety, which impact performance. A cultural neuropsychology of sport thereby concretely connects proximate and ultimate mechanisms.